Analisis Sisa Cadangan Reservoir Pada Sumur X Lapangan Y - Priska Vernanda Hipui; Jan Friadi Sinaga; Mirza; Baiq Maulinda Ulfah; Mohammad Lutfi; Luthfiyah Atisa Fadhilah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2021)
Decline curve analysis: this method uses an exponential decline curve to describe the decline in reservoir production over time. This method utilizes historical production data to extrapolate and estimate the remaining reserves in the reservoir. So that the well in the field